(untitled) (Fiep Bulletin - online, 2016)
INTRODUCTION: The aging process associated with sedentary lifestyle becomes a concern when analyzing the risk of chronic degenerative diseases. Knowing the benefits of physical activity for health is common to see groups of elderly people seeking a more active life. Thus we sought to know the real effects of systematic training of gymnastics in the functional components of elderly in Triunfo-PE.OBJECTIVE: Identify the effects of gymnastics training on components of functional fitness of elderly in Triumph-PE.METHODOLOGY: Ten (10) elderly subjects were selected from sixty (60) to eighty (80) years. A physical assessment using as reference the battery of Furlleton test was performed. After twelve (12) weeks to re adopted the same procedures used at the beginning of the study was performed. In the analysis, the data of the two assessments were compared by observing the standard deviation between the values obtained in both tests.RESULTS AND DISCURTIONS: After twelve (12) weeks no loss of sampling so that the ten (10) participants of the 3rd age group underwent reassessment. All data collected showed improvement in indices of functional capacity after 12 weeks except for the agility and dynamic balance that exhibit a reduction in the indices obtained from revaluation.CONCLUSION: Systematic training of gymnastics performed between 12 weeks caused positive changes in force levels lower and upper, flexible members, as well as cardiorespiratory fitness. However the training did not influence significantly the levels of agility and dynamic balance, thus causing a reduction in this component in the elderly evaluated.